ANALISI STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUAL PRODUK SEPATU SKECHERS PADA MAL CIPUTRA DI PEKANBARU - Salis, Muhammad; Diantara, Litra; Setiawan, Adi; Kamal, Mustafa; Ali, Auzar (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study was to determine the right marketing strategy so as to increase sales and win the retail business competition. This research was conducted at the Skechers Shop Ciputra Mall Pekanbaru which is located on Riau Street No.58 1st Floor, Kampung Baru, Senapelan District, Pekanbaru City which was conducted for two months from May to June 2024. The data source of this research is from the leadership and employees, especially the marketing department, while the data analysis technique is SWOT analysis. The results showed that the company's strength map is located in quadrant I, based on the Average Total Weighted Value (TNB). TNB strength variable 1.30, weakness variable 0.79, opportunity variable 1.35 and threat variable 0.84. The company's strength position map is located in quadrant I. The strategy used by Strenghts Opportunities (SO) shows a very favorable situation for the company that must be applied is to support an aggressive growth policy (growth oriented strategy) showing the number of opportunities that must be taken as much as possible with the strengths the company has